Covid 19 Infection In A Patient Newly Diagnosed With Hiv Tb Coinfection – A Case Report (Indian Journal of Applied-Basic Medical Sciences, 2022)
Introduction -COVID 19 refers to infectious disease caused due to infection by SARS-CoV-2, which resulted in a pandemic in the year 2020, with continuing effects in some regions of the world. It chiefly causes a respiratory illness, with features ranging from fever and mild cough to breathlessness and hypoxemia, along with a secondary hyperinflammatory and hypercoagulable state. HIV/TB coinfection is, on its own, associated with a poor outcome, due to an increased propensity to secondary infections. Method & Discussion :Here, we describe the case of an elderly male admitted for COVID 19, but diagnosed as having HIV/TB coinfection, with generalised lymphadenopathy and other constitutional features. Treatment was instituted per protocol. He also developed a treatment-related immune reconstitution inflammatory syndrome (IRIS), which was appropriately managed, and was eventually discharged following recovery from COVID-19. ART and AKT, with prophylactic medications, were ongoing at the time of discharge.Conclusion :– HIV/TB coinfection is associated with a poor prognosis. There are no specific recommendations for management of superadded COVID-19. The number of reported cases is low, and treatment had been given for the respective disorders as per prevailing local protocols.
Keywords: HIV/TB coinfection; COVID 19 with HIV/TB; immune reconstitution inflammatory syndrome (IRIS); TB lymphadenopathy